2021
DOI: 10.1101/2021.12.17.21267976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sputnik Light booster after Sputnik V vaccination induces robust neutralizing antibody response to B.1.1.529 (Omicron) SARS-CoV-2 variant

Abstract: COVID-19 vaccination campaign has been launched around the world. More than 8 billion vaccines doses have been administered, according to the WHO. Published studies shows that vaccination reduces the number of COVID-19 cases and dramatically reduces COVID-19-associated hospitalizations and deaths worldwide. In turn, the emergence of SARS-CoV-2 variants of concern (VOC) with mutations in the receptor-binding domain (RBD) of S glycoprotein poses risks of diminishing the effectiveness of the vaccination campaign.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 5 publications
(4 reference statements)
0
26
0
Order By: Relevance
“…Given the urgency to assess efficacy against the upcoming VOC Omicron, most studies (with a few exceptions [21,30]) relied over Omicron pseudovirus development and neutralization assays, which, as opposed to live authentic virus, are scalable, do not require BSL-3 facilities, and provide results in less than 1 week.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the urgency to assess efficacy against the upcoming VOC Omicron, most studies (with a few exceptions [21,30]) relied over Omicron pseudovirus development and neutralization assays, which, as opposed to live authentic virus, are scalable, do not require BSL-3 facilities, and provide results in less than 1 week.…”
Section: Resultsmentioning
confidence: 99%
“…This may be a false premise for recipients of inactivated whole-virus vaccines (e.g., BBIBP-CorV or VLA2001): for BBIBP-CorV, the efficacy against Omicron is largely reduced [40,41], but the impact of boost doses is still unreported at the time of writing. For CoronaVac® (SinoVac), three doses led to 5.1 fold-reduction in nAb titer [41], while for Sputnik V nAb titer moved from a 12-fold reduction at 6-12 months up to a 7-fold reduction at 2-3 months after a boost with Sputnik Light [30].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the virus-neutralization activity of sera samples obtained from individuals vaccinated with Pfizer/BNT162b2, Moderna/mRNA-1273 or Sputnik V decreased in the case of the B.1.351, B.1.1.28/P.1 and B.1.617.2 variants compared to wild-type virus (29)(30)(31)(32). The most pronounced decrease in the virus-neutralization activity of sera is observed in the case of the B.1.1.529 (Omicron) variant (33)(34)(35). Escape mutations are also a challenge for antibody-based therapy development.…”
Section: Discussionmentioning
confidence: 96%
“…It was shown that the virus-neutralization activity of sera samples obtained from individuals vaccinated with Pfizer/BNT162b2, Moderna/mRNA-1273 or Sputnik V decreased in the case of the B.1.351, B.1.1.28/P.1 and B.1.617.2 variants compared to wild-type virus ( 30 33 ). The most pronounced decrease of the virus-neutralization activity of sera observed in case of the B.1.1.529 (Omicron) variant ( 34 36 ). Escape mutations are also a challenge for antibody-based therapy development.…”
Section: Discussionmentioning
confidence: 97%